(untitled) (مجلة إحالات, 2026)
This research addressed the effectiveness of distance education in light of technological advancements, with a focus on the "Moodle" platform as a leading educational tool in achieving such effectiveness. The study highlighted the importance of distance education in providing flexible and interactive learning environments, benefiting from digital developments to overcome the constraints of time and space. Special attention was given to the role of Moodle as an open-source electronic learning environment that supports both self-directed and collaborative learning through assessment tools, course management, and enhanced interaction between teachers and learners. The results showed that utilizing Moodle contributes to improving academic achievement and developing learners’ self-directed skills, provided that good planning and proper training on using the platform are ensured. The research concluded by emphasizing the importance of integrating modern interactive platforms to sustain the effectiveness of distance education and improve its outcomes.